Room-Temperature, Base-Mediated Selective Synthesis of 2-(Arylamino)ethanols and 2-Aryloxyethanols - Sonawane, Rahul B.; Sonawane, Swapnali R.; Rasal, Nishant K.; Jagtap, Sangeeta V. (SynOpen, 2019)
A simple and efficient protocol for base-mediated selective synthesis of 2-(arylamino)ethanols from primary aromatic amines and 2-aryloxyethanols from phenols, promoted by K2CO3 has been achieved under mild conditions. Even in presence of excess alkyl halide, selective mono-N-alkylation has been achieved. Tolerance of a variety of functional groups is demonstrated by 15 examples of selective N-alkylation of aromatic amines and 19 examples of O-alkylation of phenols. The efficacy of the protocol is demonstrated by the formal synthesis of Ticlopidine®, Vildagliptin®, Quetiapine®, and Gemfibrozil®.
Keywords: selective N-alkylation; 2-(arylamino)ethanols; amines; 2-aryloxyethanols; phenols; K2CO3 promoted; Na2CO3 controlled